Multiculturalism Integration in Islamic Education: A Systematic Review of Contemporary Practices and Theoretical Frameworks - Viky Nur Vambudi; Mahasri Shobahiya; Musa Asy'arie; Muh. Nur Rochim Maksum; Muhammad Badat Alauddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to explore the implementation of multiculturalism in Islamic education across various contexts and regions, and its contribution to a more inclusive and tolerant understanding of Islam. This research employs a Systematic Literature Review method, yielding 9 articles from the Scopus database. The findings indicate that multiculturalism in Islamic education effectively reduces tensions between religious and ethnic groups, while shaping individuals who respect differences in culture and belief. In Indonesia, Islamic moderation values have proven effective in fostering a more harmonious society. In Malaysia, Australia, and the United Kingdom, multicultural Islamic education plays a significant role in enhancing social cohesion. However, implementation remains challenged by limited resources, inadequate educational policies, and difficulties in designing curricula that effectively accommodate diversity. This study recommends enhanced teacher training, improved educational policies, and the development of more inclusive curricula to maximize the effectiveness of multicultural Islamic education.